PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. DUTAPALMA NUSANTARA PERKEBUNAN SEI. KUANTAN KABUPATEN KUANTAN SINGINGI - Gunawan Gunawan; Zulfadil Zulfadil; Taufiqurrahman Taufiqurrahman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The study was conducted at PT. Dutapalma Nusantara Perkebunan Sei. Kuantan Kabupaten Kuantan Singingi. Aims to determine the effect simultaneously and partially variable Compensation And Work Discipline Of Employee Productivity. There are trhee variables: the dependent variable is Employee Productivity and two free variables Compensation And Work Discipline. The study was conducted using a sample of 72 people. Research using test equipment and multiple linear regression analysis using sampling techniques with Slovin method by giving questionnaires to respondents. Increased employee productivity through compensation and work discipline on PT. Dutapalma Nusantara Perkebunan Sei. Kuantan Kabupaten Kuantan Singingi simultaneously significant effect on the productivity of employees working. Compensation and working discipline partial effect on employee productivity. These results show that with the right policies and the compensation received by the employee as well as increased work discipline tergas will increase the productivity of employees on PT. Dutapalma Nusantara Perkebunan Sei. Kuantan Kabupaten Kuantan Singingi.Keywords : Compensation, Work Discipline, and Employee Productivity